47.4k views
2 votes
Substitution
3x - y=4
2x-3y=-9

1 Answer

4 votes


\bf \begin{cases} 3x-y=4\\ 3x=4+y\\ 3x-4=\boxed{y}\\[-0.5em] \hrulefill\\ 2x-3y=-9 \end{cases}\implies \qquad \stackrel{\textit{substituting on the 2nd equation}}{2x-3\left( \boxed{3x-4} \right)=-9}


\bf 2x-9x+12=-9\implies -7x+12=-9\implies -7x=-21 \\\\\\ x = \cfrac{-21}{-7}\implies \blacktriangleright x = 3 \blacktriangleleft \\\\\\ \stackrel{\textit{since we know that}}{3x-4=y}\implies 3(3)-4=y\implies 9-4=y\implies \blacktriangleright 5 = y \blacktriangleleft \\\\[-0.35em] ~\dotfill\\\\ ~\hfill (3~~,~~5)~\hfill

User Lavvo
by
5.6k points